IMPACT OF ELECTRICITY SERVICES ON UNEMPLOYMENT IN NIGERIA - OLUSEGUN, KAZEEM LEKAN; NURAINI, HASHIMU SALAUDEEN; ADELEKE, ADENIKE ADEDAYO (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2025)
This study empirically investigates the impact of electricity on unemployment in Nigeria for the period of 1970-2020 using time series data obtained from statistical bulletin of the Central Bank of Nigeria (CBN, 2021) and the National Bureau of Statistics (NBS, 2021). Autoregressive Distributed Lag (ARDL) technique was employed to test the short-run and long-run impacts. The study found evidence of a negative and statistically significant impact of electricity (megawatt per hour of electricity generation and consumption) on unemployment rate both in the short-run and long-run. However, there exists non-significant impact of electricity transmission losses on unemployment rate. On the basis of these empirical findings, the study recommends an urgentneed for the electricity distribution companies to step-up electricity supply to Nigerian firms in order to accelerate the growth of enterprises, enhance jobs creation and reduces unemployment. Increasing electricity access to business firms should involve upgrading and expansion of the national grid particularly the electricity generation capacity and distribution network. The transmission company of Nigeria should ensure that transmission lines are rehabilitated in order to reduce power and technical faults in existing transmission and distribution infrastructure so as to increase generation capacity. When these are achieved, path to industrialization and economic growth to curtail unemployment are guaranteed.